Implementasi Trigatra Bahasa dalam Upaya Optimasi Peran Duta Bahasa Jawa Barat - Intishar, Nabilah Amartya; Hardini, Tri Indri; Sunendar, Dadang (Universitas Pendidikan Indonesia, 2023)
The attitude of speakers towards language is one of the influences on language preservation and shifting. Language Ambassador is one of the platforms that has an important role in implementing Trigatra Bahasa. This study aims to (1) describe whether the West Java Language Ambassador is the right means to be a means of implementing the Trigatra Bahasa; (2) describe the form of implementation of the Trigatra Bahasa in the West Java Language Ambassador; and (3) describe the impact of the implementation of the Trigatra Bahasa in the West Java Language Ambassador. The findings of this research were obtained through a questionnaire distributed to the West Java Language Ambassador Finalists. The questionnaire contains open and closed questions related to optimizing the role of Language Ambassadors in the effort to implement the Trigatra Bahasa. This research used a mixed method convergent design type. This method collects quantitative and qualitative data simultaneously to be able to describe the collected data. In general, the results of this research shows that West Java Language Ambassadors have a positive assessment category towards optimizing their role in efforts to implement the Trigatra Bahasa. However, the regional language aspect still has a fairly negative assessment category. It shows that there is a need for further deepening of understanding in the aspect of regional language. Furthermore, the results of this research are implied for the development of language ambassador selection strategies and language preservation by the government.